THE INHIBITORY EFFECT OF GALANGIN ON CYTOKINES AND NITRIC OXIDE IN MICROGLIA BV2 CELL LINE - Al-Abd, Nazeh M.; Kassim, Mustafa; Zajmi, Asdren (Malaysian Journal of Science, 2017)
Galangin is an active flavonoid compound found in various plants, and is one of the primary constituents of honey and propolis. It has antioxidant, anti-inflammatory, antimicrobial and hepatoprotective properties. This study is intended to evaluate the effects of galangin on cytokines and nitric oxide (NO) secretion from microglia BV2 after being induced with lipopolysaccharide. Microglia BV2 was incubated with Galangin (with and without LPS) and dexamethasone for 24h. NO production in the cultured supernatant was measured with the Griess reaction. IL-6, IL-10, and TNF-Î± levels were measured using immunoassay. Results indicated that galangin did not exert cytotoxicity effect on the cell viability of BV2 macroglia at concentrations less than 40 Âµg/mL. It was also observed that galangin had significantly suppressed the production of cytokines, such as IL-6, IL-10 and TNF-Î±, as well as NO in LPS-induced BV2 cells. The antioxidant and anti-inflammatory properties of galangin are associated with its ability to inhibit NO and cytokines. Our results further showed the potential impact of galangin, thus suggesting that further development is feasible in order to leverage on its promising antioxidant and anti-inflammatory effects in treating neuroinflammatory diseases. Key words: Galangin; Lipopolysaccharide (LPS); Nitric oxide (NO); Cytokines; Microglia BV2.